Struggle and Tension in City in Nayan Raj Pandey’s Ular - Subedi, Yubaraj (NPRC Journal of Multidisciplinary Research, 2025)
Background: Nayan Raj Pandey’s Ular [Imbalance] (1998) portrays Nepalgunj and Kathmandu as contested urban landscapes where systematic exploitation, political corruption, economic disparity, and social marginalization define the lives of the underprivileged. Methods: This study employs qualitative literary analysis to examine the urban struggle in Ular. Theoretical framework from Mumford’s (2019) concept of the city as a social institution and a theatre of social action, Wirth’s (1938) idea of corruption, exploitation, and lack of emotional ties, Simmel’s (2023) individualism, alienation, impersonal nature, and blasé attitude of metropolis, and Nandy’s (2001) estrangement and alienation ground the analysis, situating Ular within South Asian urban discourse. Results: Ular depicts Nepalgunj as a contested space where the poor struggle for survival amid the indifference of political elites. Similarly, Kathmandu embodies the ultimate seat of power, reinforcing social hierarchies and discrimination rather than offering respite and help. Premlalwa’s economic precarity and Draupadi’s dehumanizing exploitation reveal cities as hostile urban labyrinths driven by indifference and corruption. Conclusion: Ular reveals Nepali cities as landscapes of continuous struggle, where urbanization perpetuates social hierarchies and marginalization. The novel also reflects the precarious realities of urbanization in Nepal, where cities function not as spaces of empowerment but as landscapes of continuous struggle. Novelty: By analyzing Ular through urban studies lenses, this study uniquely situates Nepali literature within global urban discourses, illuminating the precarious realities of South Asian urbanization.